Gambaran Pengetahuan Dan Keterampilan Mahasiswa Keperawatan Anestesiologi Universitas Harapan Bangsa Tentang Pemeriksaan LEMON Pada Pra Anestesi - Lyna Lyvia Br.Hutagaol; Septian Mixrova Sebayang; Ema Wahyu (Khatulistiwa Nursing Journal, 2025)
Background: The LEMON assessment serves as a reliable predictor to identify intubation difficulties in airway evaluation, neck mobility limitation being the most important factor associated with intubation challenges. The LEMON assessment is important for anesthesiology students to learn to be able to recognize potential difficulties when intubating, especially in patients with unexpected conditions. Objective: This study aims to determine the level of knowledge and skills of anesthesiology nursing students at Harapan Bangsa University about the LEMON assessment in pre-anesthesia. Method: This study used a quantitative descriptive method with a cross-sectional approach. Sampling was carried out using a proportionate simple random sampling technique, with a total of 68 respondents of anesthesiology nursing students level II. Data collection was carried out using questionnaires and OSCE checklist observations. Result: The results of this study showed that the average age of respondents was 19.63 years, the youngest age was 18 years old, and the oldest age was 22 years old. The majority of respondents were female, as many as 47 respondents (61.1%). The majority of students have good knowledge, as many as 45 respondents (66.2%), and skills categorized as skilled, as many as 57 respondents (83.8%). Conclution: The findings of this study indicate that the majority of students have good knowledge and skills in performing the LEMON assessment. keyword : Lemon Examination, Knowledge, Skills, Pra-anesthesia